Komparace českého a estonského systému (systémů) zdravotního a nemocenského pojištění - Daler, Jan (Univerzita Pardubice, 2016)
The paper deals with two systems - health and sickness insurance in two countries. In Czech Republic, where those systems are separated, and in Estonian Republic, where exists only health insurance, where belongs also benefits for temporary incapacity to work (the benefits falling under sickness insurance in Czech Republic). Most features of the systems are similar in both countries (such as solidarity, obligation of insurance, state guarantee), but there are also differences. The main one is that state pays for a small group of people in Estonian Republic, while state insured people cover more than half of the insured people in Czech Republic. Also one benefit is different in each country. People in Czech Republic receive compensatory benefit in pregnancy and maternity, in Estonian Republic adoptive parents receive the benefit called adoption benefit.
Comparation of Czech and Estonian system(s) of health and sickness insurance
Keywords: health insurance; sickness insurance; features; benefits of temporary incapacity to work; Estonian Republic; Czech Republic; I1; H4